2010
DOI: 10.1345/aph.1p184
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk of Medication Discrepancies and Reconciliation Errors at Admission and Discharge from an Inpatient Medical Service

Abstract: Medication reconciliation strategies should focus primarily on avoiding errors at discharge. Since medication discrepancies at admission may predispose patients to reconciliation errors, early detection of such discrepancies would logically reduce the risk of reconciliation errors. Medication reconciliation programs must implement a process for gathering accurate preadmission drug histories and must submit this information to a critical assessment of patients' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
62
7
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 21 publications
12
62
7
3
Order By: Relevance
“…Our incidence of discharge medication errors is within the 25-71% incidence found in other studies. 4,11,23 Additionally, when we probed a subset of patients who had errors on admission and discharge, we found that the distribution of types of errors (i.e. mostly errors of omission or commission) were similar to prior studies.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our incidence of discharge medication errors is within the 25-71% incidence found in other studies. 4,11,23 Additionally, when we probed a subset of patients who had errors on admission and discharge, we found that the distribution of types of errors (i.e. mostly errors of omission or commission) were similar to prior studies.…”
Section: Discussionsupporting
confidence: 73%
“…1,3,12,14,15,23,25 Several factors we found to be associated with medication reconciliation errors, such as older age and number of preadmission medications, were confirmed by others. 11,12,14,15 However, in one study fewer unintentional medication discrepancies were associated with age over 85 compared to age less than 50. 12 Herrero-Herrero et al found that the number of preadmission medications predicted unjustified discrepancies (i.e.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…20 Correctly documenting all medications on admission cannot be stressed enough, as it will contribute to the patient's safety and outcomes throughout the hospital stay and at discharge. 21,22 Once an accurate medication history is obtained, proper evaluation of these agents is required. An order to continue home medications without critical appraisal of the need to continue each agent is an unacceptable practice.…”
mentioning
confidence: 99%